Many faces of dominance: the manifestation of cohabiting companion dogs’ rank in competitive and non-competitive scenarios - Kata Vékony; Péter Pongrácz (Animal Cognition)
Abstract There are indications that companion dogs of multi-dog households form a hierarchy, maintained by formal and agonistic dominance. Although it was found that the behaviour of dogs depends on their rank in several contexts, so far, the assessment of their rank itself has been based on owner-completed questionnaires. With this research we endeavoured to find associations between rank scores from the Dog Rank Assessment Questionnaire (DRA-Q) and cohabiting dogs’ behaviour in a competitive test (Toy Possession test—32 dog pairs) and a non-competitive, citizen science scenario (Greeting test—20 dog pairs). Based on the grabbing the toy first and keeping the toy at the end variables, the dogs’ rank score provided a reliable indication of the dominant and subordinate dogs’ behaviour in the Toy Possession test. Similarly, the occurrence of dominant and submissive behaviours in the Greeting Test showed a good match with the agonistic and leadership subscores of the composite rank score from the DRA-Q. Our results provide a pioneering case for validating a questionnaire-based rank scoring method with biologically meaningful behavioural tests in the case of companion dogs. The finer analysis of the results highlighted that in the case of a multi-question scoring system, some components might provide more effective prediction of the dogs’ rank-related behaviour in some situations, while other components are more relevant in others, with traits related to agonistic dominance having relevance across contexts.